Biochemical Methane Potential from Sewage Sludge: Effect of an Aerobic Pretreatment and Fly Ash Addition as Source of Trace Elements - Huilinir-Curio, C; Castillo-Reyes, A; Montalvo-Martinez, S (Elsevier Ltd, 2017)
The effect of aerobic pretreatment and fly ash addition on the production of methane from mixed sludge is studied. Three assays with pretreated and not pretreated mixed sludge in the presence of fly ash (concentrations of 0, 10, 25, 50, 250 and 500 mg/L) were run at mesophilic condition. It was found that the combined use of aerobic pretreatment and fly ash addition increases methane production up to 70% when the fly ash concentrations were lower than 50 mg/L, while concentrations higher than 250 mg/L cause up to 11% decrease of methane production. For the anaerobic treatment of mixed sludge without pretreatment, the fly ash improved methane generation at all the concentrations studied, with a maximum of 56%. The removal of volatile solids does not show an improvement compared to the separate use of an aerobic pre-treatment and fly ash addition. Therefore, the combined use of the aerobic pre-treatment and fly ash addition improves only the production of methane. © 2017 Elsevier Ltd